Metastatic leiomyosarcoma of the thyroid gland: cytologic findings and differential diagnosis - Jiyeon Lee; Yunjoo Cho; Kyue Hee Choi; Inwoo Hwang; Young Lyun Oh (Korean Society of Pathologists & the Korean Society for Cytopathology, 2021)
Metastatic leiomyosarcoma to the thyroid is an extremely rare occurrence, and only 18 cases have been reported. Here, we report a case of a 37-year-old woman who presented with multiple masses on the scalp. Excisional biopsy was done and the mass revealed fascicles of smooth muscle fibers which showed positive staining for smooth muscle actin, thus confirming the diagnosis of leiomyosarcoma. The patient was also found to have a 0.9 cm mass within the left thyroid. Fine-needle aspiration was done and the cytological smear showed hypercellular spindle cell clusters with hyperchromatic and large nuclei. Normal thyroid follicular cells were found within or around tumor cells. In this report, we present the cytologic findings of metastatic leiomyosarcoma to the thyroid and offer differential diagnoses of the aspirated spindle cells.